THE INFLUENCE OF SOCIAL MEDIA ON CONSUMER PURCHASING DECISIONS AT UD ASSYARIF PP. SALAFIYAH SYAFI'IYAH SUKOREJO SITUBONDO - Diah Yuli Setia Rini; Arif Hariyanto; Moch. Syafi'i (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2023)
This study aimed to identify the influence of social media on consumer purchasing decisions and analyze the factors that influence that influence. This research was conducted at UD Assyarif PP. Salafiyah Shafi'iyah Sukorejo Situbondo. Data was collected through questionnaires distributed to 100 respondents who were UD Assyarif consumers. The results showed that the influence of social media on consumer purchasing decisions was significant in terms of the standard beta coefficient of 0.377. In this case, social media affects consumer perceptions of products, brand awareness, trust, and consumer loyalty. This research has practical implications for companies developing effective marketing strategies through social media. Companies can utilize social media to build brand awareness, trust, and consumer loyalty. In addition, companies should also pay attention to factors that influence the influence of social media on consumer purchasing decisions, such as age, education, and online buying experience.